The development of educational gerontology in Ukraine under martial law - S. Leknitska; I. Sakhanda (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The full-scale military invasion of the Russian Federation aggressor country into Ukraine has led to the mobilisation of Ukrainian citizens of the draft age and caused a reduction in the labour market of young and middle-aged specialists. To support the labour market and economy of Ukraine, the need arose to introduce elderly people into the educational system. Therefore, the main aim of this article was to determine the specific grounds for developing educational gerontology during the full-scale military invasion of Ukraine. The data for the research were assessed using quantitative and qualitative methods, including questionnaires, observation, and analysis of data and documents. The study of the main fields of educational gerontology chosen by elderly people revealed the following: digital technology, management, health and wellness, language and culture, creative arts, engineering and infrastructure, agriculture, and logistics and supply. Researchers of educational gerontology in the USA and European countries (including Ukraine up to February 2022) identified the main reasons for the need to include elderly persons in the educational process, namely: loneliness, mental health support, and socialisation. After February 2022, the main reasons for including the elderly in the educational process expanded to include the shortage of specialists in various fields of the economy due to the mobilisation of young and middle-aged adults into the Armed Forces of Ukraine, the tragic loss of life from the bombings of Ukrainian cities and villages, and the outflow of human resources abroad. These circumstances necessitate the development of adult learning strategies and the establishment of a network of educational gerontology institutes, which will provide mental health support for the elderly and include them in the socio-economic environment